Cognitive factors management methodology for the production of high-tech enterprises - E. N. Gorlacheva; E. M. Ivannikova (Ekonomika Nauki)
The purpose of the article is to outline the main provisions of the methodology for managing cognitive factors of production. It is shown that the processes of industrial re-industrialization, known as Industry 4.0, have led to the emergence of a new type of production resources –  cognitive factors of production. The essence of the concept of “cognitive factors of production” is determined, a structural diagram of the methodology of managing cognitive factors of production is presented. Based on the methods of system analysis, an organizational and economic management model is developed and a mechanism for integration into the general control loop of an industrial enterprise is proposed. In conclusion, conclusions are drawn about the possibility of applying the methodology of managing cognitive factors of production in a knowledge-based economy.